Fernando de Castro: Cajal's Man on the Peripheral Nervous System. Issue 5 (20th June 2019) - Ros‐Bernal, Francisco; de Castro, Fernando
ABSTRACT: Santiago Ramón y Cajal developed his initial scientific career working alone. After the publication of his opus magna ("Textura del sistema nervioso del hombre y los vertebrados") and the general recognition of the scientific environments that crystallized with the concession of the International Moscow Prize (1900), the Spanish Government decided to officially support Cajal with a laboratory and the first salaries to pay collaborators. Is then when the Spanish Neurological School births: in 1902, Francisco Tello is the first one to be incorporated. With new additions, Cajal's work is complimented in new aspects, including Neuropathologies. Fernando de Castro is one of his youngest direct disciples, one of the closest and more beloved. Fernando de Castro worked from 1916 in Cajal's lab, until the death of El Maestro. He was specially committed by Cajal to unravel different aspects of the structure of the peripheral ganglia: sensitive and vegetative. Afterward, Fernando de Castro described by first time the nature of arterial chemoreceptors in the carotid body. While trying to confirm his anatomical description with physiological demonstrations, and accumulating delays because of scientific decision and the sociopolitical circumstances in Spain, Corneille Heymans was awarded with the Nobel Prize in Physiology or Medicine 1938 for his contributions to the knowledge of cardiorespiratory reflexes. The Karolinska Institutet forgot Heinrich Hering and Fernando de Castro in their decision. Undoubtedly, Fernando de Castro was the most important disciple of Cajal working in the different structures of the peripheral nervous system, and this work is now reviewed here. Anat Rec, 303:1206–1214, 2020. © 2019 American Association for Anatomy